Reinforcement-concrete ratio of building frames - Tan, Chin Keng (2010)
The ratio of reinforcement-concrete is the measurement of reinforcement content in reinforced concrete. Higher the ratio means higher content of reinforcement in the reinforced concrete and it will increase the cost of the reinforced concrete frame. The objectives of this research are to determine the reinforcement-concrete ratio for the element of frame based on the categories of buildings which are 1 to 5 storey height and buildings which are more than five-storey height and whether there is significant difference in the reinforcement-concrete ratio for the element of frame between buildings of not more than fivestorey and more than five-storey height. Secondary data on the quantity of reinforcement and concrete for the element of frame are collected from the elemental cost analyses available at The Malaysian Surveyor (the professional journal of the Institution of Surveyors, Malaysia). The results of this research show that the mean reinforcement-concrete ratios for the building categories of 1 to 5 storey height and more than 5 storey height are 188.70kg.m3 and 242.23kg/m3 respectively. Findings of this research conclude that the buildings which are in the category of more than 5 storey height are having higher reinforcement concrete ratio compared to buildings which are in the category of 1 to 5 storey height and the difference is statistically significant.